Efecto del abonamiento orgánico en el crecimiento inicial de tres especies forestales pioneras sembradas a campo abierto en Puerto Almendra, Loreto – Perú, 2022 - Salazar del Aguila, Rosa Maria (2024)
The effect of two doses of organic fertilizer (chicken manure) on three pioneer species Cetico blanco (Cecropia ficifolia) Cetico colorado (Cecropia sciadophylla) and Huamansamana (Jacaranda macrocarpa) planted in open field in the CIEFOR Puerto Almendra of the UNAP was determined, data were taken on growth in height, diameter at neck height, survival and mortality, the treatments were 1 and 3 kg of chicken manure and the control, 75 plants were used for each species the experimental design was a 3 x 3 factorial the results were subjected to an ANVA which determined that there were no statistically significant differences both between treatments and between species, in terms of survival it was found that the control obtained the highest percentages 95% for the white cetico, 80% for the red cetico and 47% for Huamansamana; These results preliminarily indicate that the pioneer species are ecologically adapted to grow in degraded soils and do not require fertilizers to grow better in these conditions.